Predicting violence in female forensic inpatients with substance use disorders – the utility of a gender-responsive assessment - Wolf, Viviane; Mayer, Juliane; Steiner, Ivonne; Franke, Irina; Klein, Verena; Streb, Judith; Dudeck, Manuela (Frontiers in Psychiatry, 2024)
Given that risk assessment tools are commonly based on male samples, the applicability to female offenders justice-involved women remains to be clarified. This study aimed at assessing (1) the predictive validity of the HCR-20 V3, the prevailing, yet primarily male-based violence risk assessment instrument, and (2) the incremental validity of the FAM, a gender-responsive supplement, for both inpatient violence and violent recidivism in female offenders justice-involved women. The sample included 452 female forensic inpatients with substance use disorder discharged from German forensic psychiatric care between 2001 and 2018. ROC analyses revealed good predictive accuracy for the HCR-20 V3 while the FAM failed to provide incremental validity. Further, binary logistic regression determined several predictors of violence including personality disorder, covert/manipulative behavior, suicidal behavior/self-harm, and problematic intimate relationship. These findings support the applicability of the HCR-20 V3 in female offenders justice-involved women with substance use disorder, while highlighting the clinical relevance of the FAM in supporting a gender-informed risk management.